Unconventional Monetary Policy and Asset Price Risk - Roache, Shaun (IMF Working Papers; Working Paper ;, 2013)
We examine the effects of unconventional monetary policy (UMP) events in the United States on asset price risk using risk-neutral density functions estimated from options prices. Based on an event study including a key exchange rate, an equity index, and five commodities, we find that 'tail risk' diminishes in the immediate aftermath of UMP events, particularly downside left tail risk. We also find that QE1 and QE3 had stronger effects than QE2. We conclude that UMP events that serve to ease policies can help to bolster market confidence in times of high uncertainty.